Elevated liver transaminases and their association with metabolic syndrome in type 2 diabetic patients attending tertiary care hospital of Nepal. Issue 1 (1st January 2018) - Pardhe, Bashu Dev; Kapali, Ojashpi Singh; Mathias, Jennifer; Bhetwal, Anjeela; Shakya, Jyotsna; Shrestha, Pranita; Prajapati, Meenu; Prajapati, Sajani; Adhikari Khanal, Nabina; Khanal, Puspa Raj
ABSTRACT: Background : Worldwide, the prevalence of the metabolic syndrome (MetS) is estimated to be 70% among those with type 2 diabetes mellitus (T2DM). T2DM and MetS are associated with abnormal liver enzyme levels, which can be the result of non-alcoholic fatty liver disease, cirrhosis, hepatocellular carcinoma or acute liver failure. The present study investigated the association between transaminases and MetS in T2DM patients. Methods : A descriptive cross-sectional study was conducted over the period of 6 months among 540 diabetic patients attending a tertiary care hospital in Nepal. The diagnosis of MetS was based on International Diabetes Federation (IDF), National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) and Harmonized definition 2009. Association between metabolic components and liver enzymes was established by crude and adjusted logistic regression analysis. Results : Overall, the prevalence of elevated enzyme levels was 58.9% for alanine aminotransferase (ALT), 42.2% for aspartate aminotransferase (AST) and 59.4% for gamma-glutamyl transferase (GGT). The presence of MetS was 23.3%, 36.1% and 51.9% according to NCEP ATP III, IDF and Harmonized criteria, respectively. In the binary logistic regression analysis, waist circumference > 102 cm (M) or > 88 cm (F) was only independently associated with all three elevated liver enzymes, odds ratio (OR) = 4.172 for ALT, OR = 2.795 for AST and OR = 0.245 for GGT. When all three criteria were entered for multivariate risk analysis, only the NCEP ATP III (+) was found to be associated independently with raised all three liver enzymes. Conclusion : Central obesity and MetS following NCEPATP III criteria were independently associated with elevated ALT, AST and GGT in our diabetic population. Clinicians may consider hepatic complication as a negligible component in T2DM. The present findings may encourage more attention.